Evaluation of the cytotoxic and genotoxic effects of benchmark multi-walled carbon nanotubes in relation to their physicochemical properties. (16th November 2016) - Louro, Henriqueta; Pinhão, Mariana; Santos, Joana; Tavares, Ana; Vital, Nádia; Silva, Maria João
Highlights: Cyto- and genotoxic effects of carbon nanotubes (MWCNT) in A549 and BEAS-2B cells. Correlation of the MWCNTs average size in cell culture medium with cytotoxicity. No induction of DNA damage for any MWCNTs in any cell line by comet assay. Only NM-401 and NM-402 were genotoxic in A549 cells, using micronucleus assay. Relation of biological effects and physicochemical characteristics is discussed. Abstract: To contribute with scientific evidence to the grouping strategy for the safety assessment of multi-walled carbon nanotubes (MWCNTs), this work describes the investigation of the cytotoxic and genotoxic effects of four benchmark MWCNTs in relation to their physicochemical characteristics, using two types of human respiratory cells. The cytotoxic effects were analysed using the clonogenic assay and replication index determination. A 48h-exposure of cells revealed that NM-401 was the only cytotoxic MWCNT in both cell lines, but after 8-days exposure, the clonogenic assay in A549 cells showed cytotoxic effects for all the tested MWCNTs. Correlation analysis suggested an association between the MWCNTs size in cell culture medium and cytotoxicity. No induction of DNA damage was observed after any MWCNTs in any cell line by the comet assay, while the micronucleus assay revealed that both NM-401 and NM-402 were genotoxic in A549 cells. NM-401 and NM-402 are the two longest MWCNTs analyzed in this work, suggesting that length may be determinant for genotoxicity. No induction of micronuclei was observed in BBEAS-2Beas-2B cell line and the different effect in both cell lines is explained in view of the size-distribution of MWCNTs in the cell culture medium, rather than cell's specificities.